Nonwoven material containing crimped multicomponent fibers
The nonwoven sheet with crimped multicomponent fibers, featuring a curved radial interface and optimized polyolefin polymers, addresses the need for improved softness and flexibility in sanitary products by enhancing crimp behavior and manufacturing processes.
Patent Information
- Application Number
- JP2024540785
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-05
- Filing Date
- 2023-01-03
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-01-03
AI Technical Summary
Existing nonwoven materials for sanitary products, such as infant diapers, lack optimization and diversification of polymers in crimped multicomponent fibers, leading to suboptimal softness and flexibility.
A nonwoven sheet with crimped multicomponent fibers featuring a curved radial interface between polymer components, defined by a curvature of 0.05-0.25, enhances crimp behavior and fiber properties, using polyolefin polymers like propylene homopolymers and propylene-α-olefin copolymers, with controlled crystallization and melt properties, and optionally enhanced by nucleating agents.
The solution results in improved softness, flexibility, and bulkiness of nonwoven materials, suitable for sanitary products, by optimizing crimped fiber behavior and manufacturing processes.
Smart Images

Figure 2025501352000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to nonwoven sheets comprising crimped multicomponent fibers. [Background technology]
[0002] Flat sheets of nonwoven materials are used in the hygiene industry for the large-scale production of baby diapers and similar products. To improve the comfort of the wearer of such products and their function, the industry strives to increase the softness and flexibility of the materials. Incorporating crimped multicomponent fibers into such materials instead of, or in addition to, straight monocomponent fibers is a widely documented and marketed approach to meet such demands. By using crimped fibers, the nonwoven becomes bulkier, less dense, and more flexible and soft, much like straight and curly hair. Generally, crimped multicomponent fibers contain two or more polymers of different physical properties that are distributed asymmetrically across their cross-sections, the most common being side-by-side. This configuration results in crimping of the fiber when it is subjected to physical stress, such as during drawing or quenching in the case of spunbond fibers.
[0003] One of the earliest patents on this technology is US Patent 6,454,989, originally filed by the US company Kimberly-Clark. The document describes the basic principles in the context of spunbond, which had become the industry standard for nonwoven materials for hygienic applications, and includes a long list of options in which the polymers distributed across the fiber cross-section can be different. The options mentioned include, next to a range of common degrees of difference, differences in melting point, differences in crystallization behavior, differences in melt elasticity, differences in molecular weight average or distribution, and many others. However, most of the options have not been tested in practice, and since then, much research activity has been carried out to identify conditions under which they can be used in practice, and configurations that provide materials with particularly desirable properties under various aspects. Patents resulting from these developments include EP 3165656, EP 3121314, EP 3246443, and EP 3246444, all of which date back to work done by the co-applicant of the present application. However, despite these various improvements, there remains a need for optimization and diversification of the polymers that can be used to manufacture such materials. Summary of the Invention
[0004] Against this background, the present invention proposes a nonwoven sheet comprising crimped multicomponent fibers, the fibers comprising two different polymer components (A) and (B) distributed in a parallel arrangement across the cross section of the fibers, the interface line between the two polymer components (A) and (B) contained in the radial plane of the fibers is curved and its curvature (c), defined as the quotient (h) / (b) (wherein the "baseline length" (b) is the length of an imaginary straight base line connecting the two end points of the curved interface line and the "height of curvature" (h) is the distance from the base line to the apex of the curved interface line), is between 0.05 and 0.25. The interface line has the shape of a single arc, i.e. it is not wavy or, more mathematically speaking, does not have an inflection point where the sign of the curvature changes. We restate the shape of the interface line contained in any radial plane of the fibers and thus visible when the fibers are cut radially. The radial plane is perpendicular to the longitudinal direction of the fiber and therefore at any location makes an angle of 90° with the longitudinal axis of the fiber. The shape of the radial interface line that defines the present invention is the shape of the interface line contained in this plane. This is to distinguish from the interface profile along a longitudinal or oblique line, which is naturally curved to some degree in crimped fibers due to geometric relationships. The curved nature of the radial interface line that defines the present invention is not geometrically related to the crimp of the fiber. Further research aimed at a more fundamental understanding of crimped bicomponent fibers has revealed that beneficial crimp behavior can be observed when the radial interfacial lines between the components of a multicomponent fiber in which the polymer components are arranged side-by-side have a defined curvature. In a preferred embodiment, the curvature (c) of the radial interface line is between 0.08 and 0.22, preferably between 0.10 and 0.20, more preferably between 0.12 and 0.18. Very advantageous crimp behavior has been observed in many cases where the curvature is within such ranges.
[0005] For the purposes of this application, the parallel arrangement of the polymer components (A) and (B) is obtained in standard parallel fibers, but can also be present in eccentric sheath-core fibers with a D-shaped core, the latter essentially corresponding to parallel fibers surrounded by a covering of either polymer. Nevertheless, the effect when the curvature is in the range as defined is observed in particular in bicomponent parallel fibers that contain only two polymer components distributed in a parallel arrangement over the cross section. Although the effect is observed with other fiber types such as staple fibers, in a preferred embodiment, the nonwoven material of the present invention is a spunbond material and the crimped multicomponent fibers are spunbond fibers. The sheet can contain bicomponent fibers according to the definition of the present invention, in addition to other fibers such as linear monocomponent fibers, or consist of bicomponent fibers according to the definition of the present invention. In reality, the millions of fibers forming a nonwoven material are never always identical, so the term "consisting of" must be understood in the sense that the fibers are all identical from production to production, and the vast majority of the fibers, for example more than 80% of the fibers, preferably more than 90% of the fibers, are met when they exhibit the characteristics of the present invention.
[0006] To facilitate the spinning of the spunbond multicomponent fibers of the present invention, the spunbond machine must be capable of running directly adjacent streams of two different polymers in parallel on the scale of a single fiber. The streams meet just before leaving the spinneret (die plate). The formation of the curved interface and the degree of curvature depend on the polymers used and the process conditions during drawing and quenching of the fiber. In this context, at least one of the polymer components (A) or (B) is preferably a polyolefin polymer. Also, more preferably, both the polymer components (A) and (B) are polyolefin polymers. Among the polyolefin polymers, propylene homopolymers, ethylene homopolymers, and copolymers of propylene or ethylene with other α-olefins, especially propylene-α-olefin copolymers such as propylene-ethylene copolymers or propylene-C4-C8-copolymers, are preferred. In some embodiments, propylene-ethylene copolymers are most preferred. In the given context, homopolymers are defined as polymers having a comonomer content of less than 1 weight percent, preferably less than 0.5 weight percent. The comonomer content of the copolymers of propylene or ethylene with other α-olefins is preferably between 1.0 and 5.5 weight percent. The copolymers are preferably random copolymers.
[0007] In a specifically preferred embodiment, one polymer component (A) is a propylene homopolymer and the other polymer component (B) is a propylene-α-olefin copolymer, the comonomer content of which is preferably between 1.0 and 5.5 weight percent. Furthermore, in this situation, the crystallization temperatures T c It has been found that the difference between the crystallization temperature [T c (A)] and the crystallization temperature [T c (B)] is greater than 0° C. and less than 30° C., preferably greater than 10° C. and less than 25° C., as measured by differential scanning calorimetry (DSC, ISO 11357-1 and -2).
[0008] When the polymer component (A) is a propylene homopolymer and the polymer component (B) is a propylene-α-olefin copolymer, the crystallization temperature [T c(A)] is the crystallization temperature [T c It is preferable that the degree of the resistance is higher than that of (B). In one embodiment, the curved radial interface line arches toward the polymer component with the lower crystallization temperature, preferably the propylene-α-olefin copolymer, and the polymer component with the higher crystallization temperature, preferably the homopolypropylene, has a more compact cross section. The crystallization temperature of the polymer component (A) having a higher crystallization temperature [T c The absolute value of the crystallization temperature [T c The absolute value of (B)] is preferably in the range between 80°C and 125°C, preferably in the range between 90°C and 115°C.
[0009] Crystallization temperature T of polymers (A) and (B) c is related to the chemical properties of the polymer and varies with, for example, the comonomer content, stereoregularity, or molecular weight distribution in propylene-α-olefin copolymers. Crystallization behavior and kinetics can be further influenced and balanced by the addition of a nucleating agent to one or both of the polymer components (A) and (B). Nucleating agents increase the number of sites at which crystallites begin to form, thus promoting crystallization. Suitable nucleating agents include nonitol- or sorbitol-based nucleating agents. In a preferred embodiment, the nucleating agent is an α-nucleating agent. Suitable α-nucleating agents include salts of mono- and polycarboxylic acids (e.g., sodium benzoate or aluminum tert-butylbenzoate), dibenzylidene sorbitol (e.g., 1,3:2,4 dibenzylidene sorbitol), C1-C8-alkyl substituted dibenzylidene sorbitol derivatives (e.g., methyl dibenzylidene sorbitol, such as 1,3:2,4 di(methylbenzylidene) sorbitol, ethyl dibenzylidene sorbitol, or dimethyl dibenzylidene sorbitol). nonitol), or substituted nonitol derivatives (e.g., 1,2,3,-trideoxy-4,6:5,7-bis-O-[(4-propylphenyl)methylene]-nonitol), salts of phosphoric acid diesters, such as sodium 2,2'-methylenebis(4,6,-di-tert-butylphenyl)phosphate or aluminum-hydroxy-bis[2,2'-methylene-bis(4,6-di-t-butylphenyl)phosphate], vinylcycloalkane polymers, and vinylalkane polymers. Dibenzylidene sorbitol (e.g., 1,3:2,4 dibenzylidene sorbitol), dibenzylidene sorbitol derivatives, preferably dimethyl dibenzylidene sorbitol (e.g., 1,3:2,4 di(methylbenzylidene)sorbitol), or substituted nonitol derivatives, such as 1,2,3,-trideoxy-4,6:5,7-bis-O-[(4-propylphenyl)methylene]-nonitol, sodium 2,2'-methylenebis(4,6,-di-tert-butylphenyl)phosphate, vinylcycloalkane polymers, or vinylalkane polymers, may be most preferred.
[0010] A suitable amount added is between 0.01 and 5000 ppm, preferably 0.05 to 4500 ppm, more preferably in the range of 0.1 to 4000 ppm, such as 0.15 to 3000 ppm, based on the total mass of each polymer component. The melting points T of the two polymer components m It has been identified that the difference between the α and β values is a potentially important parameter. Melting temperature T of the polymer component (A) with the higher crystallization (and melting) temperature mis preferably in the range of 155°C to 164°C (measured by DSC, ISO 11357-1 and -2). The melting temperature T m The absolute value of is preferably in the range of 142° C. to 155° C. (measured by DSC, ISO 11357-1 and -2).
[0011] Other relevant properties of a polymer include the melt flow rate MFR and the molecular weight distribution. At least one, and more preferably both, of the two polymer components (A) and (B) has a melt flow rate in the range of 15 to 120 g / 10 min (measured at 230° C. and 2.16 kg according to ISO 1133). At least the component with the higher melt flow rate, in embodiments the propylene homopolymer, preferably has a melt flow rate of less than 60 g / 10 min. The polydispersity (M w / M n ) is in the range of 4.5 to 10.0 (as measured by size exclusion chromatography in accordance with ISO 16014), preferably in the range of 5.0 to 9.0, more preferably in the range of 5.5 to 8.5. The absolute value of the difference in polydispersity between the two polymer components is preferably 0.3 or more. When polymer component (A) is a propylene homopolymer and polymer component (B) is a propylene-α-olefin copolymer, it is preferred that the polydispersity of the propylene homopolymer (A) is lower than the polydispersity of the propylene-α-olefin copolymer (B).
[0012] The difference in melt viscosity at a given temperature may also be a relevant parameter in certain circumstances. When the polymer component (A) is a propylene homopolymer and the polymer component (B) is a propylene-α-olefin copolymer, it is preferred that the melt viscosity of the propylene homopolymer (A) is lower than the melt viscosity of the propylene-α-olefin copolymer (B). In a further embodiment, at least one, more preferably both, of the two polymer components (A) and (B) has a xylene cold solubles content (XCS) in the range of 1.5-10.0% by weight, more preferably in the range of 1.5-8.0% by weight. Such amounts of xylene cold solubles (XCS) are representative of the low content in any elastomeric polymer component, such as ethylene propylene rubber, and thus in a single-phase polymer component in which no elastomeric phase is dispersed. Such systems are characterized by a fairly high xylene cold solubles content. In one embodiment, one or both of the polymer components (A) and (B) are visbroken. Visbreaking refers to the controlled cracking of polymer chains by adding a visbreaking additive to the polymer components. The cracking of polymer chains occurs at high temperatures when the polymer components are melted and extruded through the spinneret of a spunbonding machine. Suitable visbreaking additives include organic peroxides, organic hydroxylamine esters, or mercaptan compounds as a source of free radicals. The preferred dosage is between 100 ppm and 500 ppm. Visbreaking can be used to affect the viscosity, adjust the polydispersity, and even adjust the melting and crystallization behavior of the two polymer components (A) and (B) relative to one another.
[0013] In one specific embodiment of the present invention, only one of the propylene polymers (A and B) is visbroken, and the M of the propylene polymers A and B is z / M w The absolute value of the difference is from 0.3 to 10.0, preferably from 0.5 to 8.5, more preferably from 1.0 to 5.5, and further preferably from 1.5 to 4.0. In another embodiment of the present invention, both propylene polymers (A and B) are visbroken, and the M of propylene polymers A and B is z / M w The absolute value of the difference is between 0.0 and 0.3, preferably between 0.00 and 0.25, more preferably between 0.00 and 0.22, and further preferably between 0.00 and 0.15.
[0014] The findings of the present invention are not limited to fibers in which the two polymer components (A) and (B) arranged in parallel are used in a mass ratio of 50:50 in the fiber. Rather, the findings are applicable to a wide range of mass ratios, such as 90:10 to 10:90. However, the preferred mass ratios that result in significant crimp are between 80:20 and 20:80, more preferably between 70:30 and 30:70, and even more preferably between 60:40 and 40:60.
[0015] In one embodiment, the weight ratio of the polymer component (A) with the higher crystallization temperature, preferably a propylene homopolymer, to the polymer component (B) with the lower crystallization temperature, preferably a propylene-α-olefin-copolymer, is less than 50:50, meaning that the polymer component (B) with the lower crystallization temperature is present in excess in the fiber, which has been found to potentially increase crimp. In an alternative embodiment, the weight ratio of the polymer component (A) with the higher crystallization temperature, preferably a propylene homopolymer, to the polymer component (B) with the lower crystallization temperature, preferably a propylene-α-olefin-copolymer, is greater than 50:50, meaning that the polymer component (A) with the higher crystallization temperature is present in excess in the fiber, which has been found to potentially increase the stability of the manufacturing process. The crimped bicomponent fiber is typically helically crimped. In one embodiment, the average number of crimps of the crimped multicomponent fiber ranges from at least 7 crimps per cm of fiber, preferably at least 10 crimps per cm of fiber, measured under a tensile preload of 2 mg / denier according to Japanese Standard JIS L-1015-1981. The crimp amplitude is preferably less than 0.30 mm, preferably between 0.20 and 0.30 mm, measured under a tensile preload of 2 mg / denier according to JIS L-1015-1981.
[0016] The linear mass density of the fibers is preferably in the range between 1.0 and 2.2 denier, preferably between 1.2 and 2.0 denier. The basis weight of each spunbond layer in the multi-layer sheet is 4 to 40 g / m2 Between 5 and 25 g / m 2 It may be between. The density of the nonwoven sheet is preferably 60 mg / cm 3 Less than 50 mg / cm 3 These are typical values for nonwoven fabrics with crimped fibers and high bulk. In comparison, nonwoven fabrics with non-crimped fibers and standard bulk have a density of typically 60-70 mg / cm. 3 Exceeds. The thickness of the nonwoven sheet is 2500mm, in accordance with WSP.120.6, option A. 2 When measured on a plate with a pressure of 0.5 kPa, the basis weight is 20 g / m 2 Above that, it is preferably greater than 0.35 mm.
[0017] In one embodiment, the spunbond sheet forms one layer of a multi-layer sheet comprising one or more additional layers in addition to the spunbond sheet according to the invention. The additional layers may be nonwoven materials such as additional spunbond or meltblown sheets, or other sheets such as polymeric films or woven fabrics. A preferred embodiment is a multi-layer sheet in which the sheet according to the invention is combined with at least one further spunbond nonwoven sheet, preferably a spunbond nonwoven sheet formed from non-crimped fibers such as monocomponent fibers. n The sheet according to the present invention includes any SM or SMS type structure (such as SSM, SSMS, SMMS, SSMMS, etc.) in combination with one or more layers of meltblown nonwoven sheets, which may further be combined with at least one layer of a spunbond nonwoven sheet, preferably a spunbond nonwoven sheet formed from non-crimped fibers. For multi-layer sheets comprising a nonwoven sheet according to the invention, it is preferred that the nonwoven sheet according to the invention forms an outer layer of the multi-layer sheet.
[0018] In one embodiment, the nonwoven or multi-layer sheet includes a bond pattern that is introduced by a calendar roll during manufacture. In one embodiment, the bond pattern has a bond area of 10-16% and / or 20-45 dots / cm 2 dot density and / or 0.35-0.55mm per dot 2 Such a relatively open bond pattern is typical of sheets comprising high loft spunbond materials formed from crimped fibers.
[0019] The basis weight of each spunbond layer in the multi-layer sheet is 3 to 25 g / m 2 Between 4 and 20 g / m 2 The basis weight of the meltblown layer may be between 0.5 and 5 g / m 2 Between 1 and 4 g / m 2 It may be between. The present invention further relates to a method for producing a spunbond nonwoven sheet or multi-layer body as defined above. Spunbond nonwoven sheets are produced in an apparatus comprising at least two extruders having spinnerets, drawing channels, and moving belts, in which fibers are spun in the spinnerets, drawn in the drawing channels, and laid on the moving belts, and the apparatus comprises a pressurized process air cabin that directs process air through the drawing channels to draw the fibers. The drawing channel may comprise multiple sections. The drawing channel or sections of the drawing channel may narrow with increasing distance from the spinneret. In one embodiment, the convergence angle can be adjusted. The device may form a sealed assembly extending at least between the entry point of the process air and the end of the drawing channel, so that no air can enter from the outside and the supplied process air cannot escape to the outside. In one embodiment, the device comprises at least one diffuser disposed between the end of the drawing channel and the moving belt.
[0020] The pressure difference between the ambient pressure and the process air in the cabin is usually greater than 2000 Pascals. It has been observed that, within reasonable limits, higher cabin pressures tend to provide the desired range of curvature and favorably affect crimping. Thus, in a preferred embodiment, the cabin pressure is greater than 2500 Pascals, more preferably greater than 3000 Pascals, or even greater than 3500 Pascals. For process stability, at the upper limit, the cabin pressure is preferably less than 6000 Pascals, preferably less than 5000 Pascals. Suitable process air temperatures are usually greater than 10°C. However, it has been observed that, within reasonable overall limits, higher process air temperatures tend to provide the desired range of curvature and favorably affect crimp. Thus, in a preferred embodiment, the process air temperature is greater than 20°C, more preferably greater than 25°C. At the upper limit, the process air temperature is preferably less than 60°C. When two different temperatures of process air are applied to the fiber during drawing, the above description relates to the process temperature of the air that first contacts the filaments. The maximum air velocity in the drawing channel is typically greater than 50 m / s. The present invention further relates to a hygiene product comprising a nonwoven sheet or multi-layer sheet according to the invention. The sheet of the present invention can be used as a nonwoven sheet in the hygiene industry, for example in hygiene products such as adult incontinence products, baby diapers, sanitary napkins, etc. Further details and advantages of the invention emerge from the figures and examples described below. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view of a typical bicomponent side-by-side fiber without curvature. [Diagram 2] FIG. 1 is a schematic diagram of a crimped fiber. [Diagram 3] FIG. 1 is a schematic diagram of a spinning machine suitable for producing a spunbond nonwoven sheet according to the present invention. [Figure 4] FIG. 1 is a schematic diagram of a manufacturing line suitable for producing multilayer sheets according to the present invention. [Diagram 5] 1 is a SEM (scanning electron microscope) photograph of a cross section of a bicomponent parallel fiber with curved interface lines. [Figure 6] FIG. 1 is a schematic diagram of a cross section of an eccentric sheath-core fiber having a D-shaped core and a curved interface line. [Figure 7] 1 is a graph plotting material thickness versus interface curvature for several examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Figure 1 shows a schematic diagram of a cross-section of a bicomponent side-by-side fiber. Fiber F comprises first and second polymer components A and B in a side-by-side arrangement that extends over the entire length of the fiber. 2 is a schematic diagram of a portion of crimped fiber F contained in the nonwoven fabric sheet of the present invention. The fiber is curved and has a certain crimp radius and a certain crimp number. 3 shows a spinning machine 100 suitable for producing a spunbonded nonwoven fabric according to the invention. The spunbonded nonwoven fabric NW is produced from continuous fibers F of thermoplastic material, which are spun in a spinneret 101 and then passed through a cooling device 102. Between the spinneret 101 and the cooling device 102, a monomer suction device 104 is arranged for removing gas in the form of decomposition products, monomers, oligomers, etc., generated during the spinning of the fibers F. The monomer removal device 4 is equipped with a suction port or a suction gap. In the cooling device 102, process air is applied to the fiber curtain emerging from the spinneret 101 from opposite sides. The cooling device 102 is divided into two sections 102a and 102b, which are arranged in series along the fiber flow direction. Thus, process air with a higher temperature (e.g. 60°C) can be applied to the fibers at an earlier stage in the chamber section 102a, and process air with a lower temperature (e.g. 30°C) can be applied to the fibers at a later stage in the chamber section 102b. The supply of process air is via air supply chambers 105a and 105b, respectively. The cabin pressure in the chambers 105a and 105b can be the same, e.g. about 3000 Pascals above ambient pressure.
[0023] A drawing device 106, which pulls and stretches the fibers 103, is located below the cooling device 102. The drawing device includes an intermediate channel 107 that preferably converges and narrows with increasing distance from the spinneret 101. In one embodiment, the convergence angle of the intermediate channel 107 can be adjusted. After the intermediate channel 107, the fiber curtain enters a lower channel 108. The cooling device 102 and the drawing device 106, including the middle channel 107 and the lower channel 108, are formed together as a sealed assembly, which means that over the entire length of the assembly, no major air flow can enter from the outside and the main process air supplied in the cooling device 102 cannot escape to the outside. Directly below the spinneret, some fume extraction devices may be incorporated that extract a small air volume. The fibres 103 leaving the drawing device 106 are then passed through a loading unit 109. This loading unit 109 comprises two diffusers 110 and 111 arranged in succession, the diffuser 110 having a diverging section and the diffuser 111 having a converging section and an adjacent diverging section. The diffuser angles, in particular the diffuser angles of the diverging regions of the diffusers 110 and 111, are adjustable. Between the diffusers 110 and 111 there is a gap 115 through which the surrounding air is sucked into the fibre flow space.
[0024] After passing through the laying unit 109, the fibers F are deposited as a nonwoven web NW on a rotating belt 113 formed from a breathable web. A suction device 116 is disposed below the laying area of the rotating belt 113 to draw in process air, as indicated by arrows 117 in FIG. The nonwoven web NW, once deposited, is first guided through a gap between a pair of pre-compacting rollers 114 for pre-compacting the nonwoven web NW.
[0025] FIG. 4 shows a production line 200 for producing the SMS type nonwoven laminate sheet NWLS of the present invention. Specifically, the machine produces SMS type nonwoven laminated sheets NWLS, specifically SMMS H The sheet is constructed to be manufactured in the form of a sheet, where "S" represents a conventional spunbond layer, i.e., a layer formed from uncrimped fibers, "M" represents a meltblown layer, and "S H " represents a high loft spunbond layer formed from crimped bicomponent fibers. H " is a layer according to the present invention. SMS type sheets, where the spunbond structure on one side of the inner meltblown structure is high loft and the spunbond structure on one side of the inner meltblown structure is a regular spunbond sheet, are known as semi-lofty structures. The regular S layer provides mechanical stability, the M layer improves liquid barrier properties, and the lofty S layer enhances the softness and flexibility of the fabric. Production line 200 is S HFor producing the layers, a spinning machine 100 is provided, which is configured as shown in Figure 3. Two reservoirs 118a and 118b contain the two different polymer components A and B used for spinning the bicomponent fibers. An associated reservoir 119 may contain a masterbatch with additives such as, for example, nucleating agents or visbreaking additives.
[0026] Furthermore, the production line 200 comprises a rotating belt 213, a first spinning machine 220 for forming a normal S layer, which has only one polymer reservoir 218 and is configured to spin monocomponent fibers, and two meltblowing machines 230 for forming a MM bilayer meltblown structure. The machines 220, 230, and 100 are arranged successively along the rotating belt 213. Downstream of each spinner 220 and 100 is a pair of pre-compaction rollers 214 and 114. Downstream of the last spinner is a calender / embossing roll 240 for firmly bonding the layers of the laminated sheet NWLS. FIG. 5 shows an SEM (scanning electron microscope) photograph of a cross section of a bicomponent fiber having a curved interface line between the polymer components. The photograph of FIG. 5 was taken in the manner described below, which is generally the preferred method for measuring the curvature that defines the present invention. Curvature is in principle an absolute geometric property of a fiber and is independent of the method of its measurement. Naturally, a fiber will have some variation in curvature over its length, and not all fibers in a fabric sheet are the same. For practical purposes, it is most preferred to extract at least 10 fibers from a nonwoven sheet, measure the curvature of each of the extracted fibers at randomly selected positions along the length, and use the average value.
[0027] When measuring from a nonwoven sheet, the machine direction is first determined, the sheet is encapsulated in polyester or epoxy resin and disintegrated. The resulting polymer block is then cut in a cross-machine plane perpendicular to the plane of the encapsulated nonwoven sheet. The cut surface is polished to make the interface visible after etching. The cross-section of the fiber exposed on the polished cut surface is etched to remove the more amorphous of the polymer components. The end of the fiber with the most circular cross-section and thus oriented as closely as possible in the machine direction at the cut surface is selected for measurement. Small deviations in orientation can be corrected as distortions. In practice, useful fiber cross-sections are ellipses with a ratio of major axis to minor axis of less than 1.2. Preference is given to the fibers appearing circular. After taking SEM photographs in a manner generally known to practitioners, the curvature can be determined using a photo-based measuring system such as DatInf measure from DatInf GmbH.
[0028] The interface between the two polymers can be seen to be curved. More specifically, the interface line has the shape of a single arc and does not have an inflection point where the sign of the curvature changes. In this example of FIG. 5, the polymer on the left was a propylene-α-olefin copolymer with a relatively lower crystallization temperature, and the polymer on the right was a propylene homopolymer with a relatively higher crystallization temperature. The curved interface arcs toward the left, i.e., toward the propylene-α-olefin copolymer with a relatively lower crystallization temperature. The polymer component with the higher crystallization temperature has a more compact cross section.
[0029] The curvature "c" is measured and calculated according to the following description: First, the distance "b" between the intersections of the polymer surfaces is measured by drawing a line between the intersections of the polymers on the fiber surfaces. This line is an imaginary reference line. In the example shown, b is 540 pixels. Next, the height of curvature "h" is measured by drawing a perpendicular line from the reference line (usually the middle of the reference line) to the apex of the curved interface line. The length of that line corresponds to the height of curvature "h", which is 111 pixels in the example shown. The curvature is then calculated as 111 / 540 = 0.206. Figure 5 therefore shows a fibre having a curvature within the range required by the present invention. FIG. 6 illustrates how the teachings of the present invention are also applicable to eccentric sheath-core fibers having a D-shaped core. EXAMPLES
[0030] A series of options consisting of two polymers in parallel were processed in a machine as shown in Figure 3 . For all options, the basis weight of the spunbond nonwoven material sheet is 20 g / m 2 The specific polymer throughput of the spinneret 101 was about 0.52 g of polymer per minute per hole. The cabin pressure was kept approximately constant at 4000 Pascals. Other process settings were kept in the normal range for the production of crimped fibers. For example, the ceramic precompaction roller 114, which contacts the rotating belt at the exit side of the beam, was operated at a temperature of 50-70°C. The calender (not shown in FIG. 3 but located downstream of the precompaction roller 114) was operated at a temperature of 12% bond area, 1 cm 2 The calender temperature ranged from 135 to 145° C. A wide range of different polymer combinations were tested, with the main focus being on the combination of a propylene homopolymer as polymer A and a propylene-α-olefin copolymer as polymer B. The parameter varied was primarily the difference in crystallization temperature. The configurations of the individual examples are summarized in Table 1 below.
[0031] [Table 1] In the table, "CE" represents a comparative example, and "IE" represents an example of the present invention. The polymer component PP1 is the polymer Borealis HG 475 FB, a polypropylene homopolymer described on pages 17 to 20 of application WO 2017 / 118612. Polymer component PP2 is a combination of 95% by weight of PP1 and 5% by weight of a polypropylene masterbatch containing a nucleating agent. The masterbatch is described in EP 3184587 as "IE2" and is a polypropylene homopolymer MFR 230 / 2.16 with a nucleus and 8.0 g / 10 min. Polymer component PP3 is a polypropylene homopolymer prepared as follows. The catalyst used in the polymerization process of the polymer component PP3 was prepared as follows. Chemicals used: Butylethylmagnesium (Mg(Bu)(Et), BEM) 20% solution in toluene, supplied by Chemtura 2-Ethylhexanol, supplied by Amphochem 3-Butoxy-2-propanol (DOWANOL™ PnB), supplied by Dow Bis(2-ethylhexyl) citraconate, supplied by SynphaBase TiCl4, supplied by Millenium Chemicals Toluene, supplied by Aspokem Viscoplex® 1-254, supplied by Evonik Heptane, supplied by Chevron
[0032] Preparation of Mg alkoxy compounds The Mg alkoxide solution was prepared by adding a mixture of 4.7 kg 2-ethylhexanol and 1.2 kg butoxypropanol to 11 kg of a 20 wt. % solution of butylethylmagnesium (Mg(Bu)(Et)) in toluene with stirring (70 rpm) in a 20 L stainless steel reactor. The reactor contents were kept below 45° C. during the addition. After the addition was complete, mixing (70 rpm) of the reaction mixture was continued at 60° C. for 30 minutes. After cooling to room temperature, 2.3 kg g of the donor bis(2-ethylhexyl)citraconate was added to the Mg alkoxide solution while maintaining the temperature below 25° C. Mixing was continued under stirring (70 rpm) for 15 minutes.
[0033] Preparation of solid catalyst components 20.3 kg TiCl4 and 1.1 kg toluene were added to a 20 liter stainless steel reactor. With mixing at 350 rpm and keeping the temperature at 0° C., 14.5 kg Mg alkoxy compound prepared in Example 1 was added over 1.5 hours. After adding 1.7 liters Viscoplex® 1-254 and 7.5 kg heptane and mixing at 0° C. for 1 hour, the temperature of the formed emulsion was raised to 90° C. within 1 hour. After 30 minutes, mixing was stopped, the catalyst droplets were allowed to solidify and the formed catalyst particles were allowed to settle. After settling (1 hour), the supernatant liquid was siphoned off. The catalyst particles were then washed with 45 kg toluene at 90° C. for 20 minutes, followed by two heptane washes (30 kg, 15 minutes). The temperature was lowered to 50° C. during the first heptane wash and to room temperature during the second wash. The catalyst thus obtained was used with triethylaluminum (TEAL) as cocatalyst and dicyclopentyldimethoxysilane donor (D-donor) as external donor. Polymerizations were carried out in a Borstar PP type polypropylene (PP) pilot plant equipped with one loop reactor and one gas phase reactor. The polymerization conditions for PP3-based polymers are shown in Table 2.
[0034] [Table 2] The polymer thus obtained was subsequently visbroken in a co-rotating twin-screw extruder at 200-230° C. with 5% by weight of PP-MB, 500 ppm of Irganox 3114 (BASF), 500 ppm of Irgafos 168 (BASF), 500 ppm of Ceasit FI (Baerlocher) and with an appropriate amount of (tert.butylperoxy)-2,5-dimethylhexane (Trigonox 101, sold by Akzo Nobel, Netherlands) to obtain the polymer component PP3. Polymer component PP4 is a polypropylene homopolymer described in EP 2 999 721 as example "IE3". The polymer component PP5 is a commercial grade of resin Sabic 511A. The polymer component PP6 is a commercial grade of resin Basell Moplen RP248R. Table 3 below shows the physical properties of the polymer components PP1 to PP6.
[0035] [Table 3] [Table 4] *MFR is measured in accordance with ISO1133 (230℃, load 2.16kg). **Number average molecular weight (M n ), mass average molecular weight (M w ), and Z average molecular weight (M z) were determined by gel permeation chromatography (GPC) according to ISO16014-4:2003 and ASTM D 6474-99. A PolymerChar GPC instrument equipped with an infrared (IR) detector was used with three Olexis columns and one Olexis Guard column from Polymer Laboratories, and 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / L 2,6-ditertbutyl-4-methyl-phenol) as solvent at 160 °C and a constant flow rate of 1 mL / min. 200 μL of sample solution was injected per analysis. The column set was calibrated with at least 15 narrow MWD polystyrene (PS) standards in the range of 0.5 kg / mol–11500 kg / mol using universal calibration (according to ISO 16014-2:2003). The Mark-Houwink constants for PS, PE, and PP used are as specified in ASTM D 6474-99. All samples were prepared by dissolving the polymer sample to a concentration of ~1 mg / ml (at 160 °C) in TCB (same as the mobile phase) that had been stabilized up to 160 °C for PP over 2.5 h with continuous gentle shaking in the autosampler of the GPC instrument. ***Xylene soluble fraction at room temperature (Xylene cold solubles XCS, wt%): The amount of polymer soluble in xylene is determined at 25°C according to ISO 16152; 5th edition; 2005-07-01. ****Melting temperature (T m ) and crystallization temperature (T c ) is measured on a TA Instrument Q200 Differential Scanning Calorimeter (DSC) on a sample of 5-7 mg. DSC is performed in the temperature range of -30 to +225 °C at a scan rate of 10 °C / min with a heat / cool / heat cycle according to ISO 11357-1, -2, and -3 / Method C2. c ) is determined from the cooling step, and the melting temperature (T m ) is determined from the second heating step. The measured parameters for the examples in Table 1 are summarized in Table 4 below.
[0036] [Table 5] * 2500mm in accordance with WSP.120.6, Option A 2 The thickness of the fabric measured at a pressure of 0.5 kPa on a plate **Curvature was determined by the method further defined above in relation to FIG.
[0037] [Table 6] MD: Machine direction CD: Cross machine direction ***Tensile and elongation properties were determined in accordance with WSP 110.4.
[0038] FIG. 7 shows the thickness of the material (20 g / m2) as a function of bulk and fiber crimp. 2 1 shows a graph plotting the thickness of the material (measured as described above) against the curvature "c" for Examples IE1-IE6 and several additional Examples. 2 The thickness of the spunbond nonwoven fabric is about 0.28 mm, so the reference line was drawn at 0.30 mm. It becomes clear that the bulkiness, and therefore the crimping of the fiber, is most pronounced when the value of curvature "c" is between about 0.05 and about 0.25, with a peak between about 0.12 and about 0.20. This is true whether the mass ratio of polymer A to polymer B in the fiber is 50:50, 40:60, 60:40, or 70:30.
Claims
1. 1. A nonwoven sheet comprising crimped multicomponent fibers, the fibers comprising two different polymer components (A) and (B) distributed in a side-by-side arrangement across a cross-section of the fibers, The interface line between the two polymer components (A) and (B) contained in the radial plane of the fiber is curved, the curvature (c) being: [0010] (wherein the reference line length (b) is the length of an imaginary straight reference line connecting the two end points of the curved interface line, and the height of curvature (h) is the distance from the reference line to the apex of the curved interface line). and the interface line has the shape of a single arc. Nonwoven sheet.
2. The curvature (c) of the interface line is [0025] 2. The nonwoven fabric sheet according to claim 1 ,
3. 3. The nonwoven sheet according to claim 1 or 2, wherein the sheet is a spunbond nonwoven sheet and the crimped multicomponent fibers are spunbond fibers.
4. The nonwoven sheet according to any one of claims 1 to 3, wherein one polymer component (A) is a propylene homopolymer and the other polymer component (B) is a propylene-α-olefin copolymer, the comonomer content of the propylene-α-olefin copolymer being preferably between 1.0 and 5.5 weight percent.
5. The crystallization temperature of the polymer component (A) [T c (A)] and the crystallization temperature [T c (B)] is greater than 0°C and less than 30°C, preferably greater than 10°C and less than 25°C, and preferably the curved radial interface line arches toward the polymer component with a lower crystallization temperature, and the polymer component with a higher crystallization temperature has a more compact cross section.
6. The crystallization temperature [T c (A)] is preferably in the range of 90° C. to 135° C., and the crystallization temperature [T c The nonwoven sheet according to any one of claims 1 to 5, wherein the absolute value of (B)] is preferably in the range between 80°C and 125°C.
7. 7. The nonwoven sheet of any one of claims 1 to 6, wherein one or both of the polymer components (A) and (B) comprises a nucleating agent, preferably a nonitol- or sorbitol-based nucleating agent, the nucleating agent being preferably present in an amount between 0.15 ppm and 3000 ppm.
8. The melting temperature [T m (A)] is preferably in the range between 155° C. and 164° C., and the melting temperature [T m The nonwoven sheet according to any one of claims 1 to 7, wherein the absolute value of (B)] is preferably in the range between 142°C and 155°C.
9. The melt flow rate of one or both of the polymer components (A) and (B) is 15 to 120 g / 10 min (measured according to ISO 1133 at 230° C. and 2.16 kg) and / or the polydispersity (M w / M n 9. The nonwoven fabric sheet according to claim 1, wherein the polydispersity difference between the two polymer components is preferably 2.5 to 10.0 (as measured by size exclusion chromatography in accordance with ISO 16014), and preferably the absolute value of the difference in polydispersity between the two polymer components is preferably 0.3 or more.
10. 10. The nonwoven sheet according to any one of the preceding claims, wherein one or both of the polymer components (A) and (B) comprises a visbreaking additive, preferably an organic peroxide or an organic hydroxylamine ester, the visbreaking additive being preferably present in an amount between 100 ppm and 500 ppm.
11. The nonwoven fabric sheet according to any one of claims 1 to 10, wherein the mass ratio of the two polymer components (A) and (B) is between 80:20 and 20:80, more preferably between 60:40 and 40:
60.
12. The nonwoven fabric sheet of any one of claims 5 to 11, wherein the polymer component (B) having the lower crystallization temperature is present in excess in the multicomponent fibers.
13. A multilayer sheet comprising the spunbond nonwoven fabric sheet according to any one of claims 4 to 12, and further comprising at least one layer of a spunbond nonwoven fabric sheet and / or at least one layer of a meltblown nonwoven fabric sheet.
14. A method for producing the spunbond nonwoven sheet of any one of claims 4 to 12 or the multilayer sheet of claim 13, comprising producing the spunbond nonwoven sheet in an apparatus comprising at least two extruders having spinnerets, drawing channels, and moving belts, in which fibers are spun in the spinnerets, drawn in the drawing channels, and deposited on the moving belts, the apparatus comprising a pressurized process air cabin that directs process air through the drawing channels to draw the fibers.
15. A hygiene product comprising the spunbond nonwoven sheet according to any one of claims 1 to 12 or the multilayer sheet according to claim 14.
Citation Information
Patent Citations
Nonwoven spunbond fabric
EP3321407A1
Flexible nonwoven fabric of continuous fiber
JP1990289159A
Stretchable bulky filament nonwoven fabric and its production
JP1993125645A
Leather-like sheet-shaped material and method for producing the same
JP2005256268A
Spun-bonded nonwoven fabric laminate and method for manufacturing spun bonded nonwoven fabric laminate
JP2019131945A